2022
DOI: 10.3390/lubricants10020029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graphene Nano-Additives to Lithium Grease on the Dynamic and Tribological Behavior of Rolling Bearings

Abstract: In recent years, reduced graphene oxide (rGO) received considerable interest as a lubricant nano-additive for enhancing sliding and rolling contacts. This paper investigates the tribological and dynamic behavior of ball bearings lubricated by lithium grease at different weight percentages of rGO. Full bearing tests were conducted for experimental modal analysis, vibration analysis, ultrasonic analysis, and infrared thermography. Modal analysis indicated considerable improvements of the damping ratio values up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In general, the ROI is selected according to its potential effect in the process under study. For example, nose, cheeks, forehead, and lips might be the possible ROIs experiencing a significant change in temperature when the mood of a human is altered, 26 chest, back, face shoulder arms, and legs might be significant ROIs characterizing people during endurance exercising, 27 the rolling bearings should be the ROIs for the study of nano grease performance in bearings under transversal loads, 28 and different regions of a saddle may be the ROIs to assess the fit of such saddle during horse riding. 29 In this research, it is clear that the regions characterizing the solder joints during cooling are the solder joint itself and the near surrounding area.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the ROI is selected according to its potential effect in the process under study. For example, nose, cheeks, forehead, and lips might be the possible ROIs experiencing a significant change in temperature when the mood of a human is altered, 26 chest, back, face shoulder arms, and legs might be significant ROIs characterizing people during endurance exercising, 27 the rolling bearings should be the ROIs for the study of nano grease performance in bearings under transversal loads, 28 and different regions of a saddle may be the ROIs to assess the fit of such saddle during horse riding. 29 In this research, it is clear that the regions characterizing the solder joints during cooling are the solder joint itself and the near surrounding area.…”
Section: Resultsmentioning
confidence: 99%
“…Greases are widely recognized as excellent lubricants due to their efficient lubrication and ability to reduce the wear and friction between surfaces. Different types of greases, such as lithium grease, calcium grease, and Bentone grease, are utilized in mechanical applications based on specific needs and conditions. Recent innovations in the field include nanoparticles, which have distinct properties compared with bulk materials. Nanoparticles can be synthesized through mechanical or chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that 0.1 wt.% ZnO addition is the optimum blend, which reduces the COF and WSD by about 25% and 44%, respectively, as compared to the base oil. Also, 2D nanolayered structures such as graphene have been found to reduce friction and wear by building a uniform tribo-lm between the rubbing surfaces [45]. The effect of mixing 0.01 wt.% multilayer graphene with a wax separated from agro-waste resources on the properties of the bio-grease itself was studied under different loading and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%